2021
DOI: 10.1161/jaha.121.021003
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship Between Coronary Atheroma, Epicardial Adipose Tissue Inflammation, and Adipocyte Differentiation Across the Human Myocardial Bridge

Abstract: Background Inflammation in epicardial adipose tissue (EAT) may contribute to coronary atherosclerosis. Myocardial bridge is a congenital anomaly in which the left anterior descending coronary artery takes a “tunneled” course under a bridge of myocardium: while atherosclerosis develops in the proximal left anterior descending coronary artery, the bridged portion is spared, highlighting the possibility that geographic separation from inflamed EAT is protective. We tested the hypothesis that inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 53 publications
2
19
0
1
Order By: Relevance
“…Since then, several studies have identified genes encoding other inflammatory adipokines, such as resistin and chemerin [36,52]. Due to the lack of anatomic intervening barrier, inflammatory cytokines expressed by EAT affect coronary arteries through paracrine and vasocrine pathways [53]. Lately, it has been shown that elevated abnormal EAT proteasome leads to thicker EAT layer, more intense chronic inflammation and therefore more severe CAD [15,44,54].…”
Section: Epicardial Adipose Tissue and Coronary Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several studies have identified genes encoding other inflammatory adipokines, such as resistin and chemerin [36,52]. Due to the lack of anatomic intervening barrier, inflammatory cytokines expressed by EAT affect coronary arteries through paracrine and vasocrine pathways [53]. Lately, it has been shown that elevated abnormal EAT proteasome leads to thicker EAT layer, more intense chronic inflammation and therefore more severe CAD [15,44,54].…”
Section: Epicardial Adipose Tissue and Coronary Artery Diseasementioning
confidence: 99%
“…Epicardial adipose tissue has also been gaining interest regarding oxidative stress [53]. Recently, it has been proposed that epicardial fat in humans suffering from CAD presents higher concentration of reactive oxygen species (ROS) [58].…”
Section: Epicardial Adipose Tissue and Coronary Artery Diseasementioning
confidence: 99%
“…Epicardial adipose tissue (EAT) is a type of visceral adipose tissue surrounding the myocardium and visceral layer of the pericardium [ 7 , 8 ]. In distinct conditions, EAT can secrete pro- and anti-inflammatory factors (e.g., TNF-α, IL-6, adiponectin, and leptin) through paracrine or endocrine [ 9 , 10 , 11 ]. Evidence shows that EAT is involved in the local regulation of myocardial and coronary function by modulating lipid metabolism and energy homeostasis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The time, duration and dose factors of this mechanism and its implications for an adapted nutrition for altitude sojourns in the human metabolism are not completely understood [19]. Research at a cellular level on isolated human adipocytes in their reaction to hypoxia most often concentrates on HIF-mediated inflammatory signaling in a long-term hypoxic state in regard to obesity, cancer or cardiovascular diseases [20][21][22][23]. However, there is some research on isolated human adipocytes, which could give hints for a time dose-response-curve of leptin and GLUT1 up-and downregulation mediated by levels of HIF 1 α in hypoxia and its effects on appetite of high fat saturated nutrients at high altitude [24].…”
Section: Introductionmentioning
confidence: 99%